Oral vinorelbine and cisplatin with concomitant radiotherapy in stage III non-small-cell lung cancer: an open-label phase II multicentre trial (COVeRT study). Issue 10 (November 2015) - Singhal, Nimit; Mislang, Anna; Karapetis, Christos S.; Stephens, Sonya; Borg, Martin; Woodman, Richard J.; Pittman, Kenneth
Abstract : Chemoradiotherapy regimens for stage III non-small-cell lung cancer (NSCLC) require ongoing evaluation. This South Australian multicentre prospective phase II study evaluated the safety, activity and outcomes of combination oral vinorelbine and cisplatin administered concurrently with radiotherapy for stage III NSCLC. Consecutive eligible patients received two cycles of oral vinorelbine 50 mg/m 2 day 1 (D1), day 8 (D8) and intravenous cisplatin 50 mg/m 2 D1 and D8 in a 21-day cycle. Chemotherapy was administered concurrently with radiotherapy at 60 Gy in 30 fractions, 2 Gy/fraction to the isocentre, all fields treated daily, 5 days a week over 6 weeks using 10 MV photons and three-dimensional conformal radiotherapy. The primary endpoint was to evaluate the progression-free survival (PFS). The secondary end points were safety, response rates and overall survival (OS). Forty-three eligible patients with stage III NSCLC – comprising 21 squamous cell carcinoma, 18 adenocarcinoma and four large cell carcinoma – were studied. Four patients did not complete the treatment. By intention-to-treat analysis, 25% showed a partial response and 65% had stable disease. None achieved a complete response. Of the 39 patients who completed protocol-specified treatment, 11 (28%) showed a partial response and 28 (72%) had stable disease. The median PFS was 25.2 months and the median OS was 48.3 months. Toxicities were manageable and generally mild, with the majority being either grade 1 ( n =38) or grade 2 ( n =21). Toxicities were mainly of oesophagitis, pneumonitis, fatigue, nausea and dysphagia. Two cycles of chemotherapy with oral vinorelbine and cisplatin administered concurrently with radical radiation had an acceptable toxicity profile and was active in inoperable stage III NSCLC. PFS and OS outcomes were encouraging. This regimen warrants further investigation.